Optimal production policy for economic production lot-sizing model with preventive maintenance. Issue 1 (2nd January 2021) - Park, Minjae
ABSTRACT: In this study, we determine the optimal manufacturing quantity for an economic production lot-sizing model with a defective rate and preventive maintenance for a manufacturing machine. We investigate the properties of economic manufacturing quantity to minimize expected costs during the production run when a random defective rate for that product is considered using an in-control condition and an out-of-control condition. If a manufacturing machine produces a proportion of defective items which is larger than the lot tolerance percent defective, then a machine shifts from an in-control condition to an out-of-control condition, and it should have a maintenance service to decrease the possibility that it will produce imperfect-quality products. A research model is developed to determine optimal manufacturing quantity and optimal production time when a defective rate and maintenance service are considered. Numerical examples are given for the applicability of the methodology derived in the paper.